Whole langiuage, learning styles, and multiple intel-ligences in EFL - Ghosn, Irma K. (1998)
Whole language, learning styles and multiple intelligences are all buzzwords that have flooded the educational market with seminars, conferences and instructional materials that claim to cater to these theories. This article does not claim to present “the way to do whole language with learning styles and multiple intelligences”, but attempts, by presenting selected strategies, to raise readers’ awareness of the many possibilities that may exist and that may facilitate students’ language learning, especially within the constraints that EFL teachers often operate